Plasma D‐Dimer Concentrations during Experimental EHV‐1 Infection of Horses. (20th September 2013) - Goehring, L.S.; Soboll Hussey, G.; Gomez Diez, M.; Benedict, K.; Maxwell, L.K.; Morley, P.S.; Sloet van Oldruitenborgh‐Oosterbaan, M.M.; Lunn, D.P.
<x xml:space="preserve">Abstract</x> Background Central nervous system blood vessel thrombosis is a part of the pathogenesis of equid herpesvirus‐associated myeloencephalopathy (EHM). D‐dimers (DD) are stable breakdown products of cross‐linked fibrin, and increased DD‐plasma concentrations could reflect the degree of systemic coagulation during EHV‐1 infection. Hypothesis We hypothesized that blood DD concentrations will be increased during periods of EHV‐1 fever and viremia, reflecting an activated coagulation cascade with fibrinolysis. Animals Twenty‐eight equids were infected with EHV‐1 in 3 experimental infection studies. Three (uninfected) horses were included in a separate study to evaluate methodology for DD concentration measurements. Methods Clinical data and quantitative viremia were evaluated, and DD concentrations were measured in blood samples on the day before the infection and during days 1–12 postchallenge. Uninfected horses were sampled every 3 hours for 48 hours. Logistic and linear regression was used to investigate the potential association between the fever and viremia with the presence or absence of DD concentrations in peripheral blood. Results DD concentrations were increased for 1–8 days in the majority of infected animals. Both viremia (odds ratio [OR] 6.3; 95% confidence interval [CI] 3.4–11.8; P = .0013) and fever (OR 4.9; CI 2.3–10.1; P = .001) were strongly associated with the likelihood of detecting DD in peripheral blood. Conclusions and Clinical Importance EHV‐1 viremia is associated with increases in DD concentration in horses and ponies. This indicates that EHV‐1 viremia can lead to an activation of coagulation and fibrinolysis.